Treaty interpretation by the WTO Appellate Body - Damme, Isabelle Van. (Oxford : Oxford University Press, 2009)
This text analyses the law of treaty interpretation as applied by the WTO Appellate Body. By focusing on the development of the law in practice, and the intersection of customary international law principles with the growth of WTO specific law, the book reveals the complexity of treaty interpretation in a major international law forum.
Description based on print version record.
Keywords: Commercial treaties -- Interpretation and construction; World Trade Organization. -- Appellate Body